Preparation of biofunctionalized quantum dots using microfluidic chips for bioimaging - Hu, Siyi (2014)
Biofunctionalized quantum dots (QDs), especially protein-coated QDs, are known as useful targeted fluorescent labels for cellular and deep-tissue imaging. These nanoparticles can also serve as efficient energy donors in fluorescence resonance energy transfer (FRET) binding assays for multiplexed sensing of tumor markers. However, current preparation processes for protein-functionalized QDs are laborious and require multiple synthesis steps (e.g. preparing them in high temperature, making them dispersible in water, and functionalizing them with surface ligands) to obtain high quality and quantity of QD formulations. This significantly impedes the progress of employing QDs for clinical diagnostics use such as QDs-based immunohistofluorescence assay. Here, we demonstrate a one-step synthesis approach for preparing protein-functionalized QDs by using microfluidic (MF) chip setup. Using bovine serum albumin (BSA) molecules as the surface ligand model, we first studied and optimized the MF reaction synthesis parameters (e.g. reaction temperature, channel width and length) for making protein-functionalized QDs using COMSOL simulation modeling followed by experimental verification. Moreover, in comparison with the BSA-functionalized QDs synthesized from conventional bench-top method, BSA-QDs prepared using MF approach exhibit a much higher protein-functionalization efficiency, photostability and colloidal stability. The proposed one-step MF synthesis approach will provide a rapid, cost effective, and small-scale production of nanocrystals platform for developing new QD formulations in applications ranging from cell labeling to sensing of biomolecules. Most importantly, this approach will greatly reduce the chemical waste produced during the trial-and-error stage of developing and perfecting the desired physical and optical property of new QDs materials.